2020
DOI: 10.21203/rs.3.rs-74196/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The effects of vitamin D on albuminuria relative to blood lead in patients with type 2 diabetes

Abstract: Background: Environmental lead exposure has been linked with reduced kidney function. However, evidence about its role in diabetic kidney damage, especially when considering the nutritional status of vitamin D, is sparse. Methods: This observational study comprised 4,033 diabetic patients from seven communities in Shanghai, China. The associations of blood lead with urinary albumin-to-creatinine ratio (UACR) and albuminuria, defined as UACR ≥30 mg/g, according to serum 25-hydroxyvitamin D [25(OH)D] levels were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…But usually, the damping performance and corrosion resistance of this series of alloys are difficult to balance, and ensuring damping performance often requires sacrificing its corrosion resistance [70]. By adding different contents of Mn to Mg-3Ni alloys, Wan et al [71] found that the corrosion resistance and the damping capacity after exceeding critical strain increased as the content of Mn increased. This could provide a good method for improving the damping performance of these alloys in the future.…”
Section: Mg-ni Damping Magnesium Alloysmentioning
confidence: 99%
“…But usually, the damping performance and corrosion resistance of this series of alloys are difficult to balance, and ensuring damping performance often requires sacrificing its corrosion resistance [70]. By adding different contents of Mn to Mg-3Ni alloys, Wan et al [71] found that the corrosion resistance and the damping capacity after exceeding critical strain increased as the content of Mn increased. This could provide a good method for improving the damping performance of these alloys in the future.…”
Section: Mg-ni Damping Magnesium Alloysmentioning
confidence: 99%
“…In the Mg-3Sn-1Mn-xLa alloy, the Mn element is wholly dissolved in the α-Mg matrix and plays a solid solution strengthening role [33,42,43]. The size and distribution of the Mg 2 Sn and Sn 3 RE 5 phases have a significant impact on the mechanical properties of alloys [9,11,44,45].…”
Section: Strengthening Mechanismsmentioning
confidence: 99%